Monetary policy during the energy price crisis: ECB could have contained inflation earlier - Gökhan Ider; Alexander Kriwoluzky; Frederik Kurcz; Ben Schumann (DIW Weekly Report, 2024)
Following the end of the coronavirus pandemic, the European Central Bank (ECB) was confronted with an unprecedented increase in energy prices. This led to consumer price inflation in the euro area far beyond the ECB's inflation target of two percent, at times up to 10 percent. At the same time, the euro area economy was threatened by a recession, which resulted in the ECB facing conflicting objectives of stabilizing the economy and combating inflation. Estimates show that while the ECB's policy strategy of maintaining a low level of interest rates did improve the economy, it also exacerbated the rise in energy prices. The empirical analysis demonstrates that an interest rate hike at the beginning of the energy crisis would have stabilized inflation more effectively. Tightening monetary policy would have curbed energy demand and caused the euro to appreciate, which would have led to a more rapid decline in energy prices. In this counterfactual scenario, the euro area would have had to endure a brief recession, but the overall economic situation would have stabilized by the fourth quarter of 2023. The ECB would likely have been better able to follow its price stability mandate if a capital markets and fiscal union existed in the euro area.
Keywords: C32; E31; E52; Q43; 330; monetary policy; inflation; energy prices; optimal policy